Saving behaviour in Turkey: Where are we? and what can we do about it? - Tatlıyer, Mevlüt (Palgrave Macmillan, 2018)
The Turkish aggregate saving rate plummeted in the late 1990s and early 2000s and has not recovered fully since then. However, roughly one-half of the fall in the aggregate saving rate can be attributed to the rapid increase in education and health expenditures, which can easily be regarded as investments under broader saving definitions. In addition, one-third of the decrease in the private saving rate in the 2000s is spurious and the other two-thirds are mostly associated with durable goods consumption. Limiting credit expansion and improving credit composition, which can be done by, for example, developing Islamic financial instruments and creating wealth and pension funds, can induce households to save more and boost the productivity level of the whole economy.
Keywords: D14; E21; Investment; Private Saving Rate; Saving Behaviour; Saving Definition; Saving Rate